Evaluasi Penerapan Ketentuan Unsur Pembiayaan Pada Pendapatan Kontrak Sesuai PSAK 72 - Daniel Bohal Marisi (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2020)
In PSAK 72 paragraphs 61-63 there is a statement governing the significant funding requirements which are the conditions for calculating the benefit adjustment. The compensation adjustment can be applied with the criteria for payment within a certain time. This study aims to evaluate the application of rewards to construction companies with time criteria beyond those required by PSAK 72. Case study at PT. X is done with a qualitative approach to financial data that has been audited by external auditors, company regulations and interviews with relevant respondents. This research will use the method of calculating the time value of money to measure the adjustment of rewards on work contracts owned by PT. X as a measurement in determining the level of difference between calculation methods with and without using the time value of money.